IN LITERARY WORKS, THE DEPICTION OF HISTORICAL CHRONICLES REQUIRES A COMMITMENT TO REALISM AND AUTHENTICITY (Konferensiyalar | Conferences, 2024)
The article analyzes the portrayal of historical figures in the story "The Sun Was Not in the Sky" by the talented poet and publicist Khurshid Davron. The story highlights significant figures in the history of the Uzbek people, focusing on their activities and socio-political influence. The article primarily examines the roles of these historical figures in the story and how closely they align with historical facts. Additionally, it explores Davron's artistic style and his unique approach to presenting historical truth. Through the depiction of these figures, the author’s perspective on past events and how he conveys them to the readers is revealed.